Investigation of the gas dispersion and mixing characteristics in column flotation using Computational Fluid Dynamics (CFD) - Mwandawande, Ikukumbuta (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.